ANALYSIS AND STRATEGY FOR PROVIDING CLEAN WATER TO THE SURROUNDING COMMUNITY IN THE MUARA ANGKE AREA - Wijaya, Septihani Michella; Putri, Angely Olivia; Wijaya, Andi (Graduate Program of Universitas Tarumanagara, 2023)
The environment provides a number for humans, one of which is providing clean water that can meet human needs. Earth as a place for human life provides 97.5 percent of water and the rest is land for living. Of the 97.5 percent figure, only 2.5 percent of the water has quality for human consumption. This means that the availability of clean water consumed by humans is very limited. In addition to this, there are many other factors that cause the availability of clean water to dwindle. For this reason, efforts are needed to reduce the clean water crisis. Researchers have formulated several strategies to address clean water in the Muara Angke area. Suggested strategic programs: Educate to increase awareness about clean water aims to provide the community with the importance of keeping the environment clean to help reduce and prevent the scarcity of clean water in the community, Ultrafiltration Technology which creates and provides water suitable for use for various daily household activities -days, Reverse Osmosis System to improve water quality with a reverse osmosis system, namely water filtration processing to neutralize tastes, odors and harmful substances, Pipeline systems related to the distribution of clean water to be distributed to every community settlement, Collaboration with Air Si Biru to obtain facilities and access to drinking water from Si Biru more easily and at a more affordable price, Integrated Marketing Communication which educates the message that the importance of clean water and the condition of clean water is limited in its availability in several areas of Indonesia waste, and CSR which will improve water quality which will later be processed into water that will be used by the community.